World scientific production on biofloc technology in tilapiculture as a driver of sustainable development (Research, Society and Development, 2021)
The purpose of this review study was to evaluate the economic, social and environmental sustainability of biofloc biotechnology in the cultivation of Nile tilapia Oreochromis niloticus. With a systematic review, it was used as methodology the details of the exclusion and inclusion criteria adopted for the selection of the sample and analysis of the content of the publications. The articles used in this study were searched on the Scopus and Web of Science databases. As for the analysis, the meta-analysis was used, opting for the mixed nature, that is, qualitative and quantitative of articles published in scientific journals from 2008 to 2021. It was found that the economic, social and environmental assessment that contemplates sustainable development is found. if in the initial phase of approach, in view of the number of articles that contemplate the subject, in the analyzed period. The studies carried out using the biofloc technology belong mainly to the technical order, followed by the sustainability of the technology used, positive aspects in relation to the economic scope, however, there is a deficit in the approach of the social aspects involved with the application of this biotechnology.